The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.0014-3820.2004.tb00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: The Size-Complexity Rule

Abstract: Abstract. It is widely accepted that bigger entities have a greater division of labor than smaller ones and this is reflected in the fact that larger multicellular organisms have a corresponding increase in the number of their cell types. This rule is examined in some detail from very small organisms to large animals, and plants, and societies. Compared to other size-related rules, the size-complexity rule is relatively rough and approximate, yet clearly it holds throughout the whole range of living organisms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 16 publications
3
44
0
Order By: Relevance
“…It has been repeatedly reported that over the tree of life organismal complexity is positively correlated with size, in particular with cell number (5,62) and colony size (15,63). Our model shows that a priori module number has no influence on the strength of selection for functional specialization because condition Eq.…”
Section: Discussionmentioning
confidence: 63%
“…It has been repeatedly reported that over the tree of life organismal complexity is positively correlated with size, in particular with cell number (5,62) and colony size (15,63). Our model shows that a priori module number has no influence on the strength of selection for functional specialization because condition Eq.…”
Section: Discussionmentioning
confidence: 63%
“…Group size is positively correlated with the degree of reproductive and non-reproductive division of labour in multicellular organisms (e.g. volvocine algae [3] and ants [4,5]). Individuals in a group can specialize on a set of tasks required for the efficient functioning of the group, leading to division of labour.…”
Section: Introductionmentioning
confidence: 99%
“…Living organisms have generally become increasingly large, complex, and diverse over nearly 4 billion years of evolutionary history (Maynard Smith and Szathmáry 1995;Bonner 2004;DeLong et al 2010). At critical transitions, these increases occurred when existing entities formed collectives-genes into genomes, cells into metazoans, indi-viduals into eusocial societies, and species into mutualisms (Bourke 2011).…”
Section: Introductionmentioning
confidence: 99%